Relationship of Soil-transmitted Helminth and Enterobius vermicularis Infection with Anemic in Students in Aceh Besar - Faisal Heri; A. A. Depari; Merina Panggabean (Global Medical & Health Communication (GMHC), 2020)
Helminthiasis is a disease caused by parasites in the form of worms, one of which is the type of soil-transmitted helminth (STH),  A. lumbricoides, T. trichiura, N. americanus, and A. duodenale which infect humans through soil transmission. Enterobius vermicularis is the most common intestinal parasite in the whole world. Worms that live in the human intestine can cause malnutrition and anemic. This study aims to determine the relationship STH and Enterobius vermicularis infection with anemic of students in several elementary schools in Aceh Besar regency, Aceh province. This study was an analytical study using a cross-sectional study design conducted from May to November 2015. The sample consisted of the total sampling of 736 elementary school students, as well as using the inquiry method of Kato with stool specimens, cellophane tape anal swab, and hemoglobin. The correspondents who suffered from anemia and STH type helminthiasis, namely ancylostomiasis 7/7 students (100%, p=0.000); trichuriasis 30/58 students (51.7%, p=0.000) and 28 students not anemic (48.3%); and ascariasis 13/22 students (59.9%, p=0.002) and 9 students not anemic (41.1%). In enterobiasis infection, anemic students were 46/146 students (31.5%) and nonanemic students were 100 students (68.5%, p=0.634). In conclusion, all STH types related to the anemic status of the correspondent, and no correlation between anemic and infection of enterobiasis. HUBUNGAN INFEKSI SOIL-TRANSMITTED HELMINTH DAN ENTEROBIUS VERMICULARIS DENGAN ANEMIA PADA SISWA DI KABUPATEN ACEH BESAR PROVINSI ACEHKecacingan adalah penyakit yang disebabkan oleh parasit berupa cacing, salah satunya jenis soil-transmitted helminth (STH), yaitu A. lumbricoides, T. trichiura, N. americanus, dan A. duodenale yang menginfeksi manusia melalui transmisi tanah. Enterobius vermicularis adalah parasit usus yang paling umum di seluruh dunia. Cacing yang hidup di usus manusia ini dapat menyebabkan kurang gizi dan anemia. Penelitian ini bertujuan mengetahui hubungan infeksi STH dan Enterobius vermicularis dengan anemia pada siswa sekolah dasar di Kabupaten Aceh Besar, Provinsi Aceh. Penelitian ini merupakan penelitian analitik menggunakan rancangan cross-sectional study yang dilaksanakan dari bulan Mei sampai November 2015. Sampel berupa total sampling 736 siswa sekolah dasar, serta menggunakan metode pemeriksaan Kato dengan spesimen feses, cellophane tape anal swab, dan hemoglobin. Koresponden yang menderita anemia dan kecacingan jenis STH, yaitu ancylostomiasis 7/7 siswa (100%, p=0,000); trichuriasis 30/58 siswa (51,7%; p=0,000) dan 28 siswa tidak anemia (48,3%); serta askariasis 13/22 siswa (59,9%; p=0,002) dan 9 siswa tidak anemia (41,1%). Pada infeksi enterobiasis, siswa yang anemia adalah 46/146 siswa (31,5%) dan tidak anemia 100 siswa (68,5%; p=0,634). Simpulan, semua kecacingan jenis STH berhubungan erat dengan status anemia pada koresponden, serta tidak terdapat hubungan antara anemia dan infeksi enterobiasis.